Updates on Anticancer Therapy-Mediated Vascular Toxicity and New Horizons in Therapeutic Strategies - Hsu, Po-Yen; Mammadova, Aynura; Benkirane-Jessel, Nadia; Désaubry, Laurent; Nebigil, Canan G. (Frontiers in Cardiovascular Medicine, 2021)
Vascular toxicity is a frequent adverse effect of current anticancer chemotherapies and often results from endothelial dysfunction. Vascular endothelial growth factor inhibitors (VEGFi), anthracyclines, plant alkaloids, alkylating agents, antimetabolites, and radiation therapy evoke vascular toxicity. These anticancer treatments not only affect tumor vascularization in a beneficial manner, they also damage ECs in the heart. Cardiac ECs have a vital role in cardiovascular functions including hemostasis, inflammatory and coagulation responses, vasculogenesis, and angiogenesis. EC damage can be resulted from capturing angiogenic factors, inhibiting EC proliferation, survival and signal transduction, or altering vascular tone. EC dysfunction accounts for the pathogenesis of myocardial infarction, atherothrombosis, microangiopathies, and hypertension. In this review, we provide a comprehensive overview of the effects of chemotherapeutic agents on vascular toxicity leading to hypertension, microvascular rarefaction thrombosis and atherosclerosis, and affecting drug delivery. We also describe the potential therapeutic approaches such as vascular endothelial growth factor (VEGF)-B and prokineticin receptor-1 agonists to maintain endothelial function during or following treatments with chemotherapeutic agents, without affecting anti-tumor effectiveness.